From the solution of the expression, it can be seen that s = 6 when t = 3 while t = 1 when s = 2.
<h3>How do we solve a mathematical expression?</h3>
Given:
(12t) = (6s) ........................ (1)
When t = 3, we can solve for s from the expression in equation (1) by substituting t = 3 into the equation as follows:
12 * 3 = 6s
36 = 6s
s = 36 / 6
s = 6
When s = 2, we can solve for t from the expression in equation (1) by substituting s = 2 into the equation as follows:
12t = 6 * 2
12t = 12
t = 12 / 12
t = 1
Learn more about mathematical expression here: brainly.com/question/12401681.
#SPJ1
I think the answer's C: $7000/$8000
That's a surprisingly easy question for high school
Answer:
C. $0.19/ounce
Step-by-step explanation:
We know that 16 ounces = 1 pound but we have 5 pounds,
So, we do 5 times 16.
We get 80 (ounces) and we divided ounces by total cost ($15.25)
We get our answer:
$0.19/ounce
Answer:
70
Step-by-step explanation:
Answer:
could you translate it
Step-by-step explanation: